Beyond bullet points : using Microsoft PowerPoint to create presentations that inform, motivate, and inspire - Atkinson, Cliff (Business skills series (Redmond, Wash.), 2011)
A guide to using Microsoft PowerPoint describes how to use stories to create effective business presentations.